Klappentexte : magazin für schwules lesen & schreiben. (Berlin : rosa Winkel Verlags- und Versand GmbH, 1980)
Fonds Suzan Daniel (FSD)
Periodiciteit : halfjaarlijks
Redactie : Pf 620304, 1000 Berlin 62
Duits
Periodiek